2007
DOI: 10.1038/modpathol.3800940
|View full text |Cite
|
Sign up to set email alerts
|

Hypomethylation-induced expression of S100A4 in endometrial carcinoma

Abstract: Expression of various S100 genes has been associated with clinically aggressive subtypes in a variety of different cancers. We hypothesized that S100A4 would be overexpressed in endometrial carcinoma compared to benign endometrium. Quantitative real-time RT-PCR (qRT-PCR) was used to quantify the mRNA level of S100A4 in benign endometrium (n ¼ 19), endometrioid adenocarcinoma (n ¼ 87), and non-endometrioid tumors (n ¼ 21). Immunohistochemistry was used to verify the results of qRT-PCR and to assess protein loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
48
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(59 citation statements)
references
References 45 publications
8
48
2
Order By: Relevance
“…The role of S100A4 in tumor progression and metastasis via induction of epithelial to mesenchymal transition (EMT) has been confirmed in many types of cancer including CRC (21).The positive relationship between S100A4 expression and aggressiveness was also observed in advanced-stage endometrial cancer (22) and bladder cancer (23). These findings suggest that S100A4 overexpression is involved in the growth, invasion, and metastasis of CRC and may serve as an indicator of the aggressiveness of CRC in the clinicopathological practice.…”
Section: Discussionmentioning
confidence: 62%
“…The role of S100A4 in tumor progression and metastasis via induction of epithelial to mesenchymal transition (EMT) has been confirmed in many types of cancer including CRC (21).The positive relationship between S100A4 expression and aggressiveness was also observed in advanced-stage endometrial cancer (22) and bladder cancer (23). These findings suggest that S100A4 overexpression is involved in the growth, invasion, and metastasis of CRC and may serve as an indicator of the aggressiveness of CRC in the clinicopathological practice.…”
Section: Discussionmentioning
confidence: 62%
“…The 18 S rRNA, ␤-actin, and Ki67 assay details have been published previously (22). Additional RT-qPCR primer sequences are listed in supplemental Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…Alternatively, hypomethylation has been described as a contributing factor for oncogene overexpression in EC. The oncogene, PAX2, (Wu et al, 2005;Shang, 2006) and the metastasis promoting gene, S100A4, (Xie et al, 2007) were shown to be hypomethylated in aggressive endometrial cancer. As survivin levels progressively increased in EC tumors, we hypothesized that progressive DNA hypomethylation could explain this expression pattern.…”
mentioning
confidence: 99%